ECOCIDE CRIME AND THE URGENCY OF CODIFICATION IN NATIONAL CRIMINAL LAW: TOWARDS ENVIRONMENTAL PROTECTION AS A COLLECTIVE RIGHT - Eko Saputra, (Proceeding International Conference on Social Sciences, 2026)
Large-scale environmental destruction, or ecocide, has gained significant attention in both international and national legal discourse due to its systemic, far-reaching, and intergenerational impacts. Although Indonesia possesses environmental legal instruments, including Law No. 32 of 2009 on Environmental Protection and Management and the criminal provisions within the new Criminal Code (KUHP), there is still no explicit regulation on ecocide. This legal vacuum creates an impunity gap for corporations and individuals committing massive ecological damage. This article examines the urgency of codifying ecocide in Indonesia's national criminal law, employing a normative-juridical approach supported by John Rawls' theory of justice, Phillipus M. Hadjon's theory of legal protection, and theories of criminalization developed by R.A. Duff and Douglas Husak. Comparative analysis with Ecuador, Bolivia, Belgium, and France further demonstrates the global trend of recognizing ecocide as an extraordinary crime equivalent to genocide and crimes against humanity. Case studies of Indonesian forest fire rulings (e.g., PT Kallista Alam and PT Adei Plantation) illustrate the normative weaknesses in current environmental law enforcement. This study finds that codification of ecocide is urgent not only to ensure repressive sanctions but also to strengthen preventive and educational functions of criminal law. The normative recommendations emphasize progressive legislation that recognizes ecocide as a serious crime, targeting individuals, corporations, and even state actors, in order to guarantee environmental protection as a collective constitutional right for present and future generations.